Hubungan Umur dan Paritas Ibu Bersalin Dengan Kejadian Pre-Eklampsia - Irna Yustiana (Akademi Kebidanan La Tansa Mashiro, 2014)
The purpose of this study to determine the relationship of age and parity with the incidence of preeclampsia in RSKIA Bandung period from August to December 2009. This study is an analytic survey with the type of case control approach. The method of sampling is done by simple random sampling a total sample of 308 women giving birth. The study tested by Chi Square test. The results of statistical analyzes based on age is known that there is no relationship between maternal age and parity with the incidence of preeclampsia in RSKIA Bandung period from August to December of 2009, with (p value = 0.284 0.05) (p value = 0.718 0 ,05).